The methodology for protection from technological hazards - Brajovic, Miodrag; Dimitrova, Silvija (Macedonian Journal of Ecology and Environment, 1993)
In this article the connection between the urban ecology and the methodology for environment protection from technological catastrophes is pointed out. That is done especially to express the fact that the urban environment is more sensitive to technological hazards than rural environ ment. The definition oftechnological catastrophes is given and in addition it is specified that the methodology for environment protection from technological catastrophes consists from: roisk assessment, risk management and emergency management. On the example of a project with title , Methodology for risk assessment ’Crom natural and technological catastrophes for city of Skopje" it is shown that it is necessary for these puproses to record existing state of technological installations. ln scope of that a catalog of hazardous materials which are manipulated in course of pursuing of technological processes must be prepared.